Pathogen profiling of Australian rabbits by metatranscriptomic sequencing. Issue 5 (22nd June 2022) - Jenckel, Maria; Hall, Robyn N.; Strive, Tanja
Abstract: Australia is known for its long history of using biocontrol agents, such as myxoma virus (MYXV) and rabbit haemorrhagic disease virus (RHDV), to manage wild European rabbit populations. Interestingly, while undertaking RHDV surveillance of rabbits that were found dead, we observed that approximately 40% of samples were negative for RHDV. To investigate whether other infectious agents are responsible for killing rabbits in Australia, we subjected a subset of these RHDV‐negative liver samples to metatranscriptomic sequencing. In addition, we investigated whether the host transcriptome data could provide additional differentiation between likely infectious versus non‐infectious causes of death. We identified transcripts from several Clostridia species, Pasteurella multocida, Pseudomonas spp ., and Eimeria stiedae, in liver samples of several rabbits that had died suddenly, all of which are known to infect rabbits and are capable of causing disease and mortality. In addition, we identified Hepatitis E virus and Cyniclomyces yeast in some samples, both of which are not usually associated with severe disease. In one‐third of the sequenced total liver RNAs, no infectious agent could be identified. While metatranscriptomic sequencing cannot provide definitive evidence of causation, additional host transcriptome analysis provided further insights to distinguish between pathogenic microbes and commensals or environmental contaminants. Interestingly, three samples where no pathogen could be identified showed evidence of up‐regulated host immune responses, while immune response pathways were not up‐regulated when E. stiedae, Pseudomonas, or yeast were detected. In summary, although no new putative rabbit pathogens were identified, this study provides a robust workflow for future investigations into rabbit mortality events.